Intracerebroventricular neuropeptide Y stimulates bile secretion via a vagal mechanism. Issue 11 (November 1992) - Farouk, M; Geoghegan, J G; Pruthi, R S; Thomson, H J; Pappas, T N; Meyers, W C
Abstract : The effect of intracerebroventricular injection of neuropeptide Y on biliary secretion was studied in conscious dogs, prepared with gastric and duodenal fistulas and cerebroventricular guides. Bile secretion was increased in a dose-dependent fashion by intracerebroventricular neuropeptide Y. The peak increase was seen after 500 pM/kg of neuropeptide Y which resulted in a 30 x 2% increase in bile flow over the period 30-150 minutes after injection. (Control: 23 x 2 (1 x 2) ml/2 hours; neuropeptide Y 500 pM/kg: 30 x 5 (1 x 1) ml/2 hours). Biliary lipid composition was not altered significantly but bicarbonate output was increased at all doses tested. Intravenous infusion of neuropeptide Y (1000 pM) for 1 hour had no significant effect. Intracerebroventricular neuropeptide Y (1000 pM/250-300 mg body weight) also increased bile flow in urethane-anaesthetised rats. This effect was abolished by cervical vagotomy. The demonstration of a central stimulation of alkaline bile flow suggests that bile secretion may be subject to central modulation.